Analisis Pengaruh Perubahan Faktor Daya Dari Lagging Menjadi Leading Di Favehotel Tasikmalaya - Jamilah, Siti; Usrah, Ifkar; Chobir, Abdul (Teknik Elektro Universitas Siliwangi, 2022)
Capacitor banks are electrical equipment to increase the power factor, which will affect the current (Amperes). However, if the capacitor bank sends more reactive power than needed, it will lead to a leading power factor. Therefore, it is necessary to identify the installed electrical load, recalculate the capacity of the capacitor bank and analyze the data on the use of the capacitor bank to avoid changes in the power factor from lagging to leading. Based on the research results, the installed electrical load is dominated by inductive loads. The impact of the leading power factor is the same as the lagging power factor. When the power factor is low, it causes a large electric current. In addition, the use of active power also affects the current value. Then the capacity of the installed capacitor bank is too large, namely 300 kVar, while the calculation results are 55 kVar. The capacitor bank control panel also does not work correctly, causing the power factor to change to lead. Therefore, it is necessary to reset the Power Factor Controller of the capacitor bank panel as well as regular and regular maintenance so that the capacitor bank panel remains in good condition.